2021
DOI: 10.7717/peerj.11510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an improved method to screen semiochemicals of insect

Abstract: Background A combination of gas chromatography-electroantennographic detection (GC-EAD) and gas chromatography-mass spectrometry (GC-MS) is typically used to screen active compounds that play a role in the regulation of insect behavior. This method uses two kinds of gas chromatography (GC) equipment and needs to compare compounds between the two chromatograms, and it is tedious and costly. To improve detection efficiency, as well as reduce costs and the rate of missed detection, we designed a system connecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(45 reference statements)
0
6
0
1
Order By: Relevance
“…In comparison to other published systems utilizing an MS with GC-EAD, the non-linear relationship between retention times on the MS versus the FID chromatograms observed in our runs may relate to our use of columns after the split which have a thickerbore than those utilized by other practitioners (0.25 mm ID on both sides of the split in the case of our previous single Y-splitter configuration, 0.32 ID and 0.15 mm ID leading to the FID/EAD and MS, respectively, in the system described here, as opposed to combinations of 0.1-0.2 mm ID in other systems, Weissbecker et al, 2004;Li et al, 2021). Using thicker-bore columns also requires longer column lengths after the split in order to maintain the vacuum on the MS, which may further exacerbate the problem.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In comparison to other published systems utilizing an MS with GC-EAD, the non-linear relationship between retention times on the MS versus the FID chromatograms observed in our runs may relate to our use of columns after the split which have a thickerbore than those utilized by other practitioners (0.25 mm ID on both sides of the split in the case of our previous single Y-splitter configuration, 0.32 ID and 0.15 mm ID leading to the FID/EAD and MS, respectively, in the system described here, as opposed to combinations of 0.1-0.2 mm ID in other systems, Weissbecker et al, 2004;Li et al, 2021). Using thicker-bore columns also requires longer column lengths after the split in order to maintain the vacuum on the MS, which may further exacerbate the problem.…”
Section: Discussionmentioning
confidence: 92%
“…Previously described GC-EAD systems that incorporated an MS have all replaced the FID with an MS (Weissbecker et al, 2004;Schott et al, 2013;Bohman and Peakall, 2014;Li et al, 2021). Balancing the vacuum at the outlet for the MS with the EAD outlet at atmospheric pressure has usually been achieved by reducing the column bore leading to the MS. Other authors have not reported whether they observed a non-linear relationship between the elution times of individual compounds at the MS outlet relative to the EAD outlet, although Li et al (2021) report using a GC calculator to work out the precise lengths of column after the effluent split that were required to obtain simultaneous elution at the antenna and MS. We found this effect to be extremely challenging to overcome in a previously tested configuration using a single Y-splitter to divide effluent between EAD and an MS, since antennal depolarizations drifted apart from corresponding peaks in the total ion chromatogram (TIC) obtained from the MS as the run progressed. Because the difference between the antennal depolarization and the corresponding peak in the chromatogram changed throughout the run (it was not simply shifted by a constant time), it was very challenging to accurately assign active compounds in complex odor blends with closely eluting peaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current proof-of-principle, GC-EAD and GC-Orbitrap MS were used sequentially. However, it is easily possible to combine EAD and MS in parallel [36,37] and omit the need to compare chromatograms [38]. In combination with Orbitrap MS, the method becomes even more powerful.…”
Section: Discussionmentioning
confidence: 99%